Cholesterol dependence of collagen and echovirus 1 trafficking along the novel α2β1 integrin internalization pathway. - Elina Siljamäki (Public Library of Science (PLoS), 2013)
We have previously shown that soluble collagen and a human pathogen, echovirus 1 (EV1) cluster α2β1 integrin on the plasma membrane and cause their internalization into cytoplasmic endosomes. Here we show that cholesterol plays a major role not only in the uptake of α2β1 integrin and its ligands but also in the formation of α2 integrin-specific multivesicular bodies (α2-MVBs) and virus infection. EV1 infection and α2β1 integrin internalization were totally halted by low amounts of the cholesterol-aggregating drugs filipin or nystatin. Inhibition of cholesterol synthesis and accumulation of lanosterol after ketoconazole treatment inhibited uptake of collagen, virus and clustered integrin, and prevented formation of multivesicular bodies and virus infection. Loading of lipid starved cells with cholesterol increased infection to some extent but could not completely restore EV1 infection to control levels. Cold Triton X-100 treatment did not solubilize the α2-MVBs suggesting, together with cholesterol labeling, that the cytoplasmic endosomes were enriched in detergent-resistant lipids in contrast to αV integrin labeled control endosomes in the clathrin pathway. Cholesterol aggregation leading to increased ion permeability caused a significant reduction in EV1 uncoating in endosomes as judged by sucrose gradient centrifugation and by neutral red-based uncoating assay. In contrast, the replication step was not dependent on cholesterol in contrast to the reports on several other viruses. In conclusion, our results showed that the integrin internalization pathway is dependent on cholesterol for uptake of collagen, EV1 and integrin, for maturation of endosomal structures and for promoting EV1 uncoating. The results thus provide novel information for developing anti-viral strategies and more insight into collagen and integrin trafficking.